Etika Menuntut Ilmu dalam Islam - Zamroji, Imam (Ta’dibuna: Jurnal Pendidikan Islam, 2018)
The essence of knowledge is not merely a transformation of knowledge or skillfulness that is aimed to gain something. More than that, knowledge is light (nur) which can illuminate soul so that one will act and behave rightly. Based on this, there is no difference between "religious knowledge’· and ·’secular knowledge." The purpose of knowledge is to get closer to Allah and to more pious. ln order for someone to be successful in studying and seeking for knowledge, he/she has to be equipped with some ethics which include sincerity, continuous praying, abstaining from sin, not arrogant, actualizing and spreading what he/she has studied/known.